1995
DOI: 10.1128/aac.39.10.2269
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and sequence of the gene encoding a cefotaxime-hydrolyzing class A beta-lactamase isolated from Escherichia coli

Abstract: Escherichia coli TUH12191, which is resistant to piperacillin, cefazolin, cefotiam, ceftizoxime, cefuzonam, and aztreonam but is susceptible to cefoxitin, latamoxef, flomoxef, and imipenem, was isolated from the urine of a patient treated with ␤-lactam antibiotics. The ␤-lactamase (Toho-1) purified from the bacteria had a pI of 7.8, had a molecular weight of about 29,000, and hydrolyzed ␤-lactam antibiotics such as penicillin G, ampicillin, oxacillin, carbenicillin, piperacillin, cephalothin, cephaloridine, ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
197
3
2

Year Published

1999
1999
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(207 citation statements)
references
References 51 publications
3
197
3
2
Order By: Relevance
“…Also, the activity spectrum among CTX-M enzymes is unusually heterogeneous. The enzyme Toho-1, which belongs to the CTX-M-2 cluster, is more susceptible to inhibition by clavulanate than tazobactam (K i , 0.6 versus 5.3 mM), 14 whereas most other CTX-M enzymes exhibit an opposite behavior. Toho-1 has a lower hydrolytic activity against penicillins and higher hydrolytic activity against ceftazidime than the "typical" CTX-M enzymes.…”
Section: Introductionmentioning
confidence: 93%
“…Also, the activity spectrum among CTX-M enzymes is unusually heterogeneous. The enzyme Toho-1, which belongs to the CTX-M-2 cluster, is more susceptible to inhibition by clavulanate than tazobactam (K i , 0.6 versus 5.3 mM), 14 whereas most other CTX-M enzymes exhibit an opposite behavior. Toho-1 has a lower hydrolytic activity against penicillins and higher hydrolytic activity against ceftazidime than the "typical" CTX-M enzymes.…”
Section: Introductionmentioning
confidence: 93%
“…In the same year, a new plasmid-mediated cefotaximase, designated CTX-M-2, with an isoelectric point different from that of CTX-M-1, was described from multidrug-resistant Salmonella enterica serovar Typhimurium [38]. In 1995, Ishii et al [39] reported a novel enzyme, Toho-1 (renamed as CTX-M-44 later), which was highly homologous to MEN-1. In the following year, nucleotide sequencing studies concluded that the deduced amino acid sequence of CTX-M-1 was identical to the reported sequence of MEN-1, and the amino acid sequence of CTX-M-2 was 84% identical to that of CTX-M-1 [40].…”
Section: Ctx-mmentioning
confidence: 99%
“…However, based on sequences and structures, there appears to be conservation of positive charge in this region that results from arginine extending from positions 220, 244, or 276 as has previously been noted. [14][15][16][17] Thus, a…”
mentioning
confidence: 99%